Influence of different cooling and lubrication techniques on material machinability in machining - Sredanović, Branislav (Strojniški vestnik, 2013)
In this paper, a novel approach to the definition of universal machinability is presented. The machinability model is based on analysing the vector of the cutting process performance. The machinability of C45E steel was analysed and evaluated according to the developed machinability definition. As the machinability criteria, cutting force, intensity of tool wear and surface roughness were used. Analysis of machinability was performed using different cooling and lubrication conditions: conventional flooding, minimum quantity lubrication (MQL) and high-pressure jet-assisted machining (HPJAM). Technological parameters were adjusted to the semi-finish regime, with the use of the highest parameter values possible. During the research, cutting forces, chip shapes, tool wear and surface roughness were monitored and measured. The influence of different cooling and lubrication techniques and the relationships between process performance indicators on C45E steel machinability are analysed.
Keywords: cooling; high-pressure jet assisted machining; hlajenje; lubrication; machinability model; mazanje; model obdelovalnosti; struženje; visokotlačno odrezavanje